Synthesis of Exo‐ and Endocyclic Enamides Through Copper‐Catalyzed Regioselective Intramolecular N‐Halovinylation. Issue 17 (28th April 2020) - Gilbert, Nicolas; Ricard, Simon; Bergeron, Jodrey; Lambolez, Pierre; Daoust, Benoit
Abstract : Cross‐couplings between amides and 1, 2‐dihaloalkenes are an efficient and straightforward way to access β‐haloenamides which, in turn, can be functionalized into complex, stereodefined enamide motifs. However, the intramolecular version of these cross‐couplings, leading to cyclic β‐haloenamides, has not been formally studied. In this paper, we report an investigation of factors affecting the efficiency of the reaction and its selectivity between potential exo and endo cyclization products. We demonstrate that exo/endo selectivity is largely determined by ring strain, whether it arises from the size of the resulting ring or from the structure of the starting compound, but that selectivity can also be modulated by varying reaction conditions. Finally, we show that resulting β‐haloenamides readily undergo transition metal‐catalyzed reactions, making this sequence a viable way to access highly functionalized cyclic enamides. Abstract : The intramolecular copper‐catalyzed cross‐coupling of 1, 2‐dihaloalkenes and amides leads to cyclic β‐haloenamides, which can participate in a second cross‐coupling reaction to efficiently synthesize highly functionalized cyclic enamides. The selectivity of the intramolecular coupling between exo‐ and endocyclic regioisomers is a crucial synthetic factor and can be influenced by the structure of the substrate and the reaction conditions.